Features of Cutaneous Microbiome in Children With Atopic Dermatitis and New Pathogenetic Therapy Options - Nikolay N. Murashkin; Alexander I. Materikin; Leonid A. Opryatin; Roman V. Epishev; Eduard T. Ambarchyan; Roman A. Ivanov; Dmitri V. Fedorov (Union of pediatricians of Russia, 2020)
Atopic dermatitis is a chronic inflammatory disease characterized by relapsing course, severe itching, erythema and dry skin due to skin barrier defects and staphylococcus infection. According to current guidelines for the treatment of atopic dermatitis (prepared by dermatological societies) the background therapy is prolonged application of emollients directly on the skin and its use during bathing. Clinical studies have shown that repeated administration of emollients moisturizes the skin, restores its barrier and normal functioning, and reduces the amount of glucocorticosteroids needed for atopic eczema therapy in infants, children and adults. The results of trials and long-term clinical practice have proven that emollients are safe and effective in patients with atopic dermatitis. This article presents the information based on the recent data concerning emollients: their characteristics, mode of action, role in atopic dermatitis treatment, and results of clinical trials conducted in such patients.